Nutrient-sensing growth hormone secretagogue receptor in macrophage programming and meta-inflammation - Da Mi Kim; Jong Han Lee; Quan Pan; Hye Won Han; Zheng Shen; Sahar Eshghjoo; Chia-Shan Wu; Wanbao Yang; Ji Yeon Noh; David W. Threadgill; Shaodong Guo; Gus Wright; et al. (Elsevier, 2024)
Objective: Obesity-associated chronic inflammation, aka meta-inflammation, is a key pathogenic driver for obesity-associated comorbidity. Growth hormone secretagogue receptor (GHSR) is known to mediate the effects of nutrient-sensing hormone ghrelin in food intake and fat deposition. We previously reported that global Ghsr ablation protects against diet-induced inflammation and insulin resistance, but the site(s) of action and mechanism are unknown. Macrophages are key drivers of meta-inflammation. To unravel the role of GHSR in macrophages, we generated myeloid-specific Ghsr knockout mice (LysM-Cre;Ghsrf/f). Methods: LysM-Cre;Ghsrf/f and control Ghsrf/f mice were subjected to 5 months of high-fat diet (HFD) feeding to induce obesity. In vivo, metabolic profiling of food intake, physical activity, and energy expenditure, as well as glucose and insulin tolerance tests (GTT and ITT) were performed. At termination, peritoneal macrophages (PMs), epididymal white adipose tissue (eWAT), and liver were analyzed by flow cytometry and histology. For ex vivo studies, bone marrow-derived macrophages (BMDMs) were generated from the mice and treated with palmitic acid (PA) or lipopolysaccharide (LPS). For in vitro studies, macrophage RAW264.7 cells with Ghsr overexpression or Insulin receptor substrate 2 (Irs2) knockdown were studied. Results: We found that Ghsr expression in PMs was increased under HFD feeding. In vivo, HFD-fed LysM-Cre;Ghsrf/f mice exhibited significantly attenuated systemic inflammation and insulin resistance without affecting food intake or body weight. Tissue analysis showed that HFD-fed LysM-Cre;Ghsrf/f mice have significantly decreased monocyte/macrophage infiltration, pro-inflammatory activation, and lipid accumulation, showing elevated lipid-associated macrophages (LAMs) in eWAT and liver. Ex vivo, Ghsr-deficient macrophages protected against PA- or LPS-induced pro-inflammatory polarization, showing reduced glycolysis, increased fatty acid oxidation, and decreased NF-κB nuclear translocation. At molecular level, GHSR metabolically programs macrophage polarization through PKA-CREB-IRS2-AKT2 signaling pathway. Conclusions: These novel results demonstrate that macrophage GHSR plays a key role in the pathogenesis of meta-inflammation, and macrophage GHSR promotes macrophage infiltration and induces pro-inflammatory polarization. These exciting findings suggest that GHSR may serve as a novel immunotherapeutic target for the treatment of obesity and its associated comorbidity.